ANALYSIS OF RELATIONSHIP BETWEEN THE USAGE OF ONLINE LOAN SERVICES AND THE WELL-BEING OF INDONESIAN USING CHI-SQUARE TEST - Chamidah, Nur; Kamiilah, Nadhira Safa; Andriani, Putu Eka; Siburian, Cynthia Anggelyn; Baihaqi, Muhammad Rizaldy; S, Salma Bethari Andjani (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2024)
Online fintech lending offers convenience by providing flexibility for both lenders and borrowers. It led to a significant increase in users. Despite this encouraging growth, it comes with risks, such as the emergence of illegal loan companies. The controversial positive and negative aspects of online loans have sparked the researchers' interest in understanding how the Indonesian public perceives the existence of online loans and whether there is a relationship between the use of online loans and the well-being of users. The data were collected through the questionnaire using Google Form and then distributed to respondents who meet the specified sample criteria, namely Indonesian, aged 17 years old or above, and still able to think rationally. The total study sample are 191 respondents, with the total male is 90 and the total female is 101. Since the results of the data gathered were in the form of categorical data, so the Chi-square test is utilized in this study. With the calculated chi-square less than the chi-square table, it showed that there is no correlation between the frequency of using online loan services and the well-being of the Indonesian people, whether based on age, level of education, or type of job. Hence, it can be concluded that the usage of online loan services is not influences the well-being of Indonesian. It is also known that public perceptions of online loans vary and cannot be generalized. However, those less prosperous, tend to agree with and appreciate the online loan services’ existence compared to those who are prosperous.